A young Alu subfamily amplified independently in human and African great apes lineages. - Zietkiewicz, E (1994)
A variety of Alu subfamilies amplified in primate genomes at different evolutionary time periods. Alu Sb2 belongs to a group of young subfamilies with a characteristic two-nucleotide deletion at positions 65/66. It consists of repeats having a 7-nucleotide duplication of a sequence segment involving positions 246 through 252. The presence of Sb2 inserts was examined in five genomic loci in 120 human DNA samples as well as in DNAs of higher primates. The lack of the insertional polymorphism seen at four human loci and the absence of orthologous inserts in apes indicated that the examined repeats retroposed early in the human lineage, but following the divergence of great apes. On the other hand, similar analysis of the fifth locus (butyrylcholinesterase gene) suggested contemporary retropositional activity of this subfamily. By a semi-quantitative PCR, using a primer pair specific for Sb2 repeats, we estimated their copy number at about 1500 per human haploid genome; the corresponding numbers in chimpanzee and gorilla were two orders of magnitude lower, while in orangutan and gibbon the presence of Sb2 Alu was hardly detectable. Sequence analysis of PCR-amplified Sb2 repeats from human and African great apes is consistent with the model in which the founding of Sb2 subfamily variants occurred independently in chimpanzee, gorilla and human lineages.